Aplikasi Kasir Toko Aldi Berbasis Web Menggunakan PHP dan MYSQL dengan Framework Laravel - Hany Maria Valentine; Lira Arum Kusumaning Thyas; Andika Putra Wijaya (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Currently, stock processing and transactions at Aldi grocery stores are still done manually, making it inefficient. This situation sometimes causes Aldi stores to experience differences in data between the income and expenditure of goods. By creating this application, user errors in recording goods expenditure are minimized. This application has been successfully built using PHP, MySQL, Laravel, Visual Studio and XAMPP. This application aims to make it easier for users to record incoming and outgoing goods and ongoing transactions so that recording is made computerized, and based on the results of black box testing, this application works with the desired output. This website can be accessed via the link http://aplikasikasirtokoaldi.my.id.